Comparison of 22G reverse-beveled versus standard needle for endoscopic ultrasound-guided sampling of solid pancreatic lesions - Alatawi, Abdullah; Beuvon, Frédéric; Grabar, Sophie; Leblanc, Sarah; Chaussade, Stanislas; Terris, Benoit; Barret, Maximilien; Prat, Frédéric (United European gastroenterology journal, 2015)
Objectives Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) using standard needles has a high diagnostic value in the evaluation of solid pancreatic masses. Fenestrated needles have been developed to improve the quality of EUS-guided tissue sampling by providing core biopsies (FNB). Methods Patients with solid pancreatic masses of >2 cm were prospectively included in our study and randomized to receive EUS sampling, using either a standard 22G FNA or a 22G Procore® FNB needle. The main study endpoint was the number of needle passes required to obtain a diagnosis in more than 90% of cases. Results We included 100 patients (male = 63, female = 37; mean age = 68.4 years) in our study. We found that 88% of the lesions were malignant, with a mean size of 32 mm. A sample adequate for diagnosis was obtained in more than 90% of cases after the second needle pass in the FNB group, versus the third needle pass in the FNA group. Slide cellularity and presence of tissue microfragments were significantly higher in the FNB group. Sensitivity for the diagnosis of malignancy was 88.4% versus 97.8% for the EUS-FNA and EUS-FNB group, respectively, while specificity for both techniques was 100%. No complications were recorded. Conclusions Although the accuracy of both needle types for proving malignancy was similar, a lower number of passes was required with the FNB needles to achieve the same contributive sample rate as with the FNA needles. FNB also improved the histopathological quality of specimens, suggesting an overall superiority of FNB sampling.